1998
DOI: 10.1161/01.hyp.31.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Target-Organ Damage in Stage I Hypertensive Subjects With White Coat and Sustained Hypertension

Abstract: Controversy remains on whether white coat hypertension is a benign clinical condition or carries an increased risk of target-organ damage. Nine hundred forty-two stage I hypertensive subjects enrolled in the HARVEST trial underwent 24-hour ambulatory blood pressure monitoring and urine collection for albumin measurement. Reliable echocardiographic data were obtained in 722 subjects. White coat hypertensive subjects were defined on the basis of three different partition values: mean daytime blood pressure <130/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
3
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 37 publications
7
96
3
2
Order By: Relevance
“…29 Other potential biologic mediators of LV hypertrophy in subjects with MetS may be certain peptide hormones, such as angiotensin II and leptin, which are secreted by white adipose tissue. 20 Our findings also suggest that the clustering of features of MetS, frequently described in WCHs, may be at least in part responsible for the cardiac abnormalities, and probably for the increased cardiovascular risk displayed in some, but not all, series regarding subjects with WCH [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . On the other hand, the greater values of both LV mass and LV chamber diameter that we observed in WCHs without MetS when compared to those of normotensive controls, seem to indicate that WCH per se, independently of MetS, may not be innocuous for the heart.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…29 Other potential biologic mediators of LV hypertrophy in subjects with MetS may be certain peptide hormones, such as angiotensin II and leptin, which are secreted by white adipose tissue. 20 Our findings also suggest that the clustering of features of MetS, frequently described in WCHs, may be at least in part responsible for the cardiac abnormalities, and probably for the increased cardiovascular risk displayed in some, but not all, series regarding subjects with WCH [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . On the other hand, the greater values of both LV mass and LV chamber diameter that we observed in WCHs without MetS when compared to those of normotensive controls, seem to indicate that WCH per se, independently of MetS, may not be innocuous for the heart.…”
Section: Discussionmentioning
confidence: 93%
“…1,2 Obviously, the use of higher limits for ambulatory BP results in higher frequencies of WCH individuals with end-organ damage. However, in previous investigations, such as the HARVEST (Hypertension and Ambulatory Recording Venetia Study) 3 and the PAMELA (Pressioni Arteriose Monitorate e Loro Associazioni) 4 studies, even when lower cutoffs of ambulatory BP were used, an association between WCH and left ventricular hypertrophy was found.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many, but not all, of these studies have demonstrated increased LVMI in WCH subjects, with LVMI intermediate between that of subjects with normotension and those with sustained hypertension. [2][3][4][5][6][7][8][9][10][11][12][13] In addition, a recent study suggests that the long-term incidence of stroke may be elevated in adults with WCH. 14 Little is known about the clinical significance and natural history of WCH in children.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] The lack of an agreed definition for WCH further adds to the confusion. Furthermore, interpretation of these studies has been made more difficult as many are not controlled for the level of ambulatory BP.…”
Section: Association With Target Organ Damagementioning
confidence: 99%